Establishment and development of the Tuvan National Library as a infoedicational and cultural hub (1993-2013) - Fencel, Olga V. (The New Research of Tuva, 2014)
Article presents the history of establishment and development of the National Library of the Republic of Tuva in the period between 1993 and 2013. New workforms that appeared during presented period are listed. The new status of the Library is underlined.